Differences in Learning Outcomes of Class VIII Students of SMP Negeri 3 Tondano on The Material of Building Flat Side Spaces Given the Implementation of The PjBL Model - Sania Veolina Br Ginting; James U. L. Mangobi; Ontang Manurung (Departement of Mathematics Education, 2024)
This study investigates the disparities in students' mathematical learning achievements when using the Flat-Side Building material in conjunction with the PjBL model compared to students who use the DI model. This study employs an experimental research approach utilizing a post-test-only control group design. The participants in this study consisted of two groups: an experimental group, comprising 25 students from class VIII-C, and a control group, comprising 24 students from class VIII-B at SMP Negeri 3 Tondano for the academic year 2023/2024. The selection of participants was done randomly from the two classes. The post-test research yielded an average score of 79.44 for the experimental class and 75.0208 for the control class. The hypothesis test analysis results indicate that the value of tcount is 2.302 and the value of ttable is 1.678. Since the value of tcount is greater than the value of ttable, we can infer that the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. This study determines that there is a discernible disparity in student learning outcomes when the subject of Building Flat Side Spaces is taught utilizing the Project-based Learning (PjBL) model as opposed to the Direct Instruction (DI) model in the eighth grade of SMP Negeri 3 Tondano.